HILIRISASI PENGGUNAAN OPERASI SUKU ALJABAR DALAM PEMBELAJARAN MATEMATIKA DI SD - Wahid Umar; Bety Miliyawati (PEDAGOGIK, 2023)
Mathematics as one of the sciences has an object of study in the form of abstract ideas and concepts and their relationships, the development of which is structured in a structured and logical process using special terms and symbols. Mathematical concepts can be utilized not only by mathematics itself but can be used or applied to other sciences. The purpose of learning mathematics in schools is to provide opportunities for students to be able to think systematically, critically, logically and creatively. For this reason, students need to be trained to be able to apply the concepts learned in mathematics in relation to everyday life. One of these efforts is by linking the concept of algebraic operations to learning mathematics in elementary schools. The application of this concept is directed at solving math problems in elementary school. This study is a literature review related to downstream learning processes and mathematical thinking habits of elementary school teacher and student prospective teachers. This is closely related to the characteristics of mathematics as a science and human activity, namely that mathematics is a pattern of thinking and/or a means to train thinking skills carefully, clearly and accurately. Therefore, the question in this research is: how to provide additional insight for elementary school teacher and student prospective teachers in creatively utilizing their existing knowledge to teach mathematics to elementary school students? The results of downstreaming the use of algebraic operations are considered appropriate, can provide additional insight to teachers and prospective elementary school students by constructing mathematical concepts through the habit of thinking mathematically.